Amorphous thermoplastic laminate manufactured article and method for producing same - Patents.com

By mixing the amorphous polymer with the crystalline polymer and heat treatment to form a semi-crystalline polymer, the problem of solvent residue in the laminated product is solved, and biocompatibility and high-quality laminated product manufacturing is achieved.

JP7627821B2Active Publication Date: 2025-02-07LUMAS POLYMERS LLC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023571162
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-08
Filing Date
2022-06-03
Publication Date
2025-02-07
Estimated Expiration
2042-06-03

AI Technical Summary

Technical Problem

The prior art cannot effectively use amorphous polymers to make 3D parts, and the residual solvent after crystallization of solvents affects biocompatibility, limiting its application in laminated products.

Method used

By mixing the amorphous polymer with the crystalline or semi-crystalline polymer in a specific proportion, and forming the semi-crystalline polymer after heat treatment, and then forming the laminated product by fusion through directional electromagnetic radiation, ensuring that the polymer does not retain solvent during the lamination process.

Benefits of technology

The amorphous properties of the polymer during lamination are achieved, solvent residues are avoided, suitable for biocompatible applications, and can form high-quality laminated products through directional electromagnetic radiation fusion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627821000001
    Figure 0007627821000001
  • Figure 0007627821000002
    Figure 0007627821000002
  • Figure 0007627821000003
    Figure 0007627821000003
Patent Text Reader

Abstract

A semi-crystalline blend polymer useful for layer-by-layer manufacturing consists of an amorphous thermoplastic polymer and a thermoplastic semi-crystalline polymer, each of which is substantially miscible with the other and blended in an amorphous / semi-crystalline weight ratio of greater than 1 to about 20. The semi-crystalline blend polymer exhibits a DSC melting peak enthalpy of at least about 3 Joules / g. The semi-crystalline polymer can be produced by blending the polymers in the weight ratios described above and heating the mixture to a temperature between the melting temperature of the semi-crystalline polymer and the glass transition temperature of the amorphous polymer. The semi-crystalline blend polymer can revert to a substantially amorphous polymer when layer-by-layer manufacturing is performed by fusing layers of the polymer powders together.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to additively manufactured articles made of thermoplastic polymers that are amorphous. In particular, the present disclosure relates to selective laser sintering of thermoplastic polymers that revert to substantially amorphous thermoplastic polymers after forming the additively manufactured article. [Background technology]

[0002] Selective laser sintering or melting (SLS or SLM) has been used to produce 3D parts by selectively sintering powder from a powder bed (see, for example, U.S. Pat. No. 5,399,633). In this method, a powder bed maintained at an elevated temperature is selectively sintered using a CO2 laser or other electromagnetic radiation source. Once the first layer is sintered, additional layers of powder are metered out and selective sintering is repeated until the desired 3D part is produced. Because the powder must be sintered or melted, SLS has been limited by the requirement to use crystalline or semi-crystalline polymers with distinct melting points, precluding the use of amorphous polymers with desired properties such as optical transparency, toughness, and elongation before break.

[0003] Recently, techniques have been described to partially crystallize amorphous polymers (e.g., polycarbonate and polyphenylsulfone) by dissolving them in a solvent at elevated temperatures (see, e.g., U.S. Patent Nos. 5,393,333 and 5,433,623). However, the use of a solvent inevitably results in the retention of residual amounts of solvent in the crystallized polymer, which precludes its use in biocompatible applications and would require environmental mitigation if it were to be used to form additive manufacturing products. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] U.S. Pat. No. 5,597,589 [Patent Document 2] International Publication No. 2020 / 006061 [Patent Document 3] International Publication No. 2017 / 033146 Summary of the Invention [Problem to be solved by the invention]

[0005] It would therefore be desirable to provide polymers that are semi-crystalline and capable of laminate manufacturing into amorphous polymeric articles that avoid one or more of the problems in the art, such as those described above. [Means for solving the problem]

[0006] It has been discovered that certain amorphous thermoplastic polymers, when blended in the proper ratios with certain crystalline or semi-crystalline thermoplastic polymers and sufficiently heat treated, provide semi-crystalline thermoplastic polymers suitable for additive manufacturing processes such as SLS. Surprisingly, these semi-crystalline polymer blends, when additively manufactured, revert to substantially amorphous polymeric articles that are free of residual solvent and have the desirable properties of the amorphous polymers.

[0007] A first aspect of the present invention is a semi-crystalline blended polymer comprising an amorphous thermoplastic polymer and a thermoplastic semi-crystalline polymer, each of which is substantially miscible with each other and blended in a weight ratio of amorphous polymer / semi-crystalline polymer from greater than 1 to 20, the blended semi-crystalline polymer exhibiting a DSC melting peak enthalpy of at least about 5 Joules / g. The blended semi-crystalline powder may be a powder suitable for additive manufacturing processes such as SLS. The DSC melting peak enthalpy is determined according to the procedure described by ASTM D3418.

[0008] A second aspect of the invention is a method of forming a semi-crystalline blended polymer comprising the steps of: a. melt blending an amorphous thermoplastic polymer and a thermoplastic semicrystalline polymer, each of which is substantially miscible with each other in a weight ratio of amorphous polymer / semicrystalline polymer of greater than 1 to about 20 to form a blend polymer; and b. heat treating the blended polymer at a temperature above the glass transition temperature of the amorphous polymer but below the melting temperature of the semicrystalline polymer for a time sufficient to crystallize the blended polymer sufficiently to achieve a semicrystalline blended polymer; Further processing of the semi-crystalline polymer, such as size reduction, may be carried out to produce powders useful for additive manufacturing processes such as SLS.

[0009] A third aspect of the invention is a method of forming an additively manufactured article, comprising the steps of: a. spreading a layer of powder of the thermoplastic semicrystalline blend polymer of the first and second embodiments; b. heating and fusing the particles of the layer in a controlled manner with directed electromagnetic radiation; c. spreading subsequent layers of the semi-crystalline blended powder and fusing each layer to the previous layer in a controlled manner with directed electromagnetic radiation to form an additive manufactured article; The layered manufactured article can surprisingly be substantially amorphous as determined by differential scanning calorimetry (DSC) at a heating or cooling rate of 20° C. / min. Whenever DSC is referred to herein, unless otherwise specified, the heating and cooling rates are understood to be 20° C. / min.

[0010] A fourth aspect of the invention is a laminated manufactured article consisting of the thermoplastic semi-crystalline blended polymer of the first aspect that has been substantially converted back to an amorphous polymer (i.e., exhibits essentially no individual DSC heat of fusion of the enthalpy peak). The semi-crystalline powder after being heated with electromagnetic radiation, fused, and in no way limited to, heated above the melting temperature and quenched, may break the crystalline structure without subsequent rearrangement upon cooling due to the blended polymer consisting of miscible and predominantly amorphous polymers. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 shows the DSC curves of the semicrystalline thermoplastic polymers used to prepare the semicrystalline blend polymers of the present invention. [Diagram 2] FIG. 1 shows the DSC curves of the amorphous thermoplastic polymers used to prepare the semicrystalline blend polymers of the present invention. [Diagram 3] FIG. 1 shows the DSC curve of a blend polymer (15% semi-crystalline polymer and 85% amorphous polymer) before heat treatment to produce the semi-crystalline blend polymer of the present invention. [Figure 4] FIG. 1 shows the DSC curve of the semi-crystalline blend polymer of the present invention (i.e., after heat treatment). [Diagram 5] FIG. 1 shows an example of a light-transmitting laminated article of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The method of achieving the semi-crystalline blended polymer of the present invention without residual solvent includes melt blending an amorphous thermoplastic polymer and a thermoplastic semi-crystalline polymer to form a blended polymer. These polymers are substantially miscible with each other. Substantially miscible means that the glass transition temperatures determined by DSC are not significantly different. Generally, the blended copolymer does not show a clear heat of enthalpy melting peak after blending. Even if there is such a peak, it is generally not enough to achieve a good powder sintered part (e.g., the peak is less than about 1 Joule / g or is too unclear).

[0013] The amorphous and semi-crystalline polymers are mixed in a weight ratio such that the blend is composed primarily of amorphous polymer but contains enough semi-crystalline polymer to sufficiently initiate crystallization of the blended polymers. The weight ratio of amorphous polymer / semi-crystalline polymer in the mixed blend can be greater than 1 up to about 20. Desirably, the ratio is from about 2 or 3 to about 15 or 10.

[0014] A semi-crystalline polymer may be any thermoplastic organic polymer that exhibits at least about 5% crystallinity to substantially complete crystallinity when heated and cooled at rates typically experienced when forming or formulating such polymers (e.g., heating and cooling rates from ambient temperature of about 25° C. to the melting temperature). That is, the polymer exhibits crystallinity without forced crystallization methods, such as those known in the art (e.g., solvent-induced crystallization, etc.). Generally, the amount of crystallinity is at least about 5%, 10%, 15%, or 20% to about 95%, 75%, 50%, or 30%. The crystallinity may be determined by any suitable method, such as those known in the art. Illustratively, the percent crystallinity can be determined by X-ray diffraction, including wide-angle X-ray diffraction (WAXD), for example, using a Rigaku SmartLab X-ray diffractometer, or by differential scanning calorimetry (DSC), for example, using a TA Instruments DSC250 differential scanning calorimeter ASTM D3418-15. Exemplary crystalline polymers may include certain polyesters, polycarbonates, polyamides, etc., depending on the chain structure.

[0015] An amorphous polymer may be any thermoplastic organic polymer that exhibits substantially no crystallinity (if any, detectable at all) when heated and cooled at the rates described in the previous paragraph (20° C. / min is exemplary as described above). Exemplary amorphous polymers may include certain polyesters, polycarbonates, polyamides, etc., depending on the chain structure.

[0016] The melt blending of the amorphous polymer and the semi-crystalline polymer may be carried out in any suitable manner and apparatus, such as those known in the art. Examples include high intensity mixers and screw extruders (e.g., single or twin screw extruders). The amount of shear may be any that is useful to facilitate blending and compounding to form a polymer blend. The extruder may have a gradient along the length of the extruder or be held at a temperature to facilitate compounding of the two polymers. The temperature may be any temperature that is sufficient to form a polymer blend, for example, just below the temperature at which a particular condensation polymer begins to degrade. Typically, the temperature may be within 100°C, 50°C, or 25°C of the melting temperature of the semi-crystalline polymer. Typical temperatures may be from about 150°C, 175°C, or 200°C to about 300°C or 250°C. The shear may be any that is typically used in the practice of compounding polymers in a compounding extruder. The time may similarly be any time sufficient to achieve a blended polymer in which the polymers are homogeneously dissolved in one another (miscible as described above). Typical times may range from a minute or two to an hour or so. The blended polymer may be extruded and shaped into any useful shape to form semi-crystalline blended polymers, such as pellets of any shape.

[0017] The blended polymer is heat treated at a crystallization temperature above the glass transition temperature of the amorphous polymer but below the melting temperature of the semicrystalline polymer for a time period that sufficiently crystallizes the blended polymer to achieve a semicrystalline blended polymer. The atmosphere can be any useful atmosphere as long as no degradation occurs to one of the polymers present in the blended polymer, in most cases air is acceptable, and water-free gases or oxygen may be utilized (e.g., nitrogen, dry air, noble gases or combinations thereof as well as vacuum).

[0018] Heat treatment may be performed by any suitable method or device or combination thereof. For example, heating may be performed in a batch or continuous oven where heat energy is derived from any manner known in the art (e.g., resistance, combustion, induction, radiant heating or conductive heating). Heating may also be performed in the blend extruder used to form the blended polymer, but it is generally desirable to separate these processes, especially for efficiencies resulting from more efficient and uniform heat transfer without disturbing shear that may prevent the desired crystallization.

[0019] The crystallization temperature is higher than the glass transition temperature (Tg) of the amorphous polymer and lower than the melting temperature (Tm) of the semi-crystalline polymer. The Tg of the amorphous polymer is lower than the Tm of the semi-crystalline polymer. Generally, the Tg of the amorphous polymer is about 20°C to 150 or 250°C lower than the Tm. The crystallization temperature may be a single temperature or may vary between the Tg and Tm during the heat treatment. For example, the crystallization temperature may be raised or lowered and held at different temperatures between the Tg and Tm, or may be slowly ramped within this temperature range over the heat treatment time. Illustratively, the Tg of the amorphous polymer is about 60°C, 80°C, or 100°C to about 140°C or 120°C, and the semi-crystalline polymer has a Tm of at least about 160°C to about 300°C, 250°C, 225°C, 200°C, or 180°C. Tm is determined from the melting peak of the DSC as described by ASTM D3418 using the midpoint of the melting peak. The Tg of an amorphous polymer is determined from a DSC plot according to ASTM D3418 using the midpoint of the glass transition temperature.

[0020] The heat treatment time may be any time sufficient to form a semi-crystalline blended polymer, and may vary somewhat depending on the temperature used within the temperature range defined by the Tg of the amorphous polymer and the Tm of the semi-crystalline polymer. Generally, a sufficient time is when the semi-crystalline blended polymer achieves a level of crystallinity (or substantial crystallinity) such that the heat of enthalpy of the melting peak is at least about 3 or 4 Joules / g, 5 Joules / g, to about 30 Joules / g, or any other feasible amount. Generally, the heat treatment is carried out in the absence of any solvent for at least 2, 4, 6, or 8 hours to 48, 36, or 24 hours.

[0021] After heat treatment, the semi-crystalline blend polymer may be ground to a desired size for use in a particular additive manufacturing process, such as SLS. Illustratively, the semi-crystalline blend polymer may be ground and classified to have a particle size useful for producing additive manufacturing articles, typically with a median particle size (D) of about 1 micrometer (μm), 10 μm, 20 μm, or 30 μm, to 150 μm, 125 μm, 100 μm, or 90 μm by volume. 50 Similarly, to allow for consistent heating and fusing of the powder, the semi-crystalline blend polymer has a D of up to 300 μm, 200 μm or 150 μm. 90 , and a D of at least 0.1 μm, 0.5 μm or 1 μm by volume 10 It is desirable to have D 90 means the particle size (equivalent spherical diameter) in the particle size distribution in which 90% by volume of the particles are equal to or smaller than that size, and similarly, D 50 means the particle size (equivalent spherical diameter) in a particle size distribution below which at least 50% by volume of the particles are smaller, and D 10means the particle size (equivalent spherical diameter) in a particle size distribution below which at least 10% by volume of the particles are. Particle size may be determined by any suitable method, such as those known in the art, including, for example, laser diffraction of a sufficient number of particles (about 100 to about 200 particles) or image analysis of photomicrographs. Exemplary laser diffractometers are those manufactured by Microtrac, such as the Microtrac S3500.

[0022] Milling may be performed by any suitable method, such as those known in the art. Illustratively, milling at a temperature at which the semi-crystalline polymer becomes brittle may be used, such as what is commonly referred to as freeze milling. In general, freeze milling temperatures may range from about below 0°C, below -25°C, below -50°C to about -75°C, -100°C, -150°C, or -190°C. Cooling may be performed by any suitable method or means, such as using dry ice or liquid nitrogen.

[0023] As an example, a suitable pair of amorphous and semi-crystalline polymers is amorphous polymethylmethacrylate (PMMA) and semi-crystalline polylactic acid (PLA). Another suitable pair is amorphous and semi-crystalline polyamide (see, for example, U.S. Pat. No. 5,391,640). PLA can be any form of PLA, such as one formed using L-lactide, D-lactide, or a combination thereof. It is desirable for the amount of L-lactide to be at least 50%, 60%, 70%, 80%, or 90% to 98% or 100% (100% may include trace amounts of D-lactide) by weight of the monomers used to make the PLA. Other polyesters, such as those known in the art that readily form crystalline or semi-crystalline polymers, may also be used with PMMA, provided they are miscible as described herein.

[0024] Each of the amorphous or semi-crystalline polymers may have any Mw to achieve blended and semi-crystalline polymers with desired characteristics. For example, PLA may have a weight average molecular weight (Mw) of about 10 kDa to 500 kDa. The melt flow rate of the PLA may be any useful for forming blended semi-crystalline polymers. Typically, the MFR is one that achieves the desired characteristics of the semi-crystalline blended polymer when combined with PMMA. In general, the MFR may be 25, 50, 60 or 70 to 90, 100, 125 or 150 grams (210°C / 10 min, 2.16 kg). Examples of suitable PLA are available under the trade names INGEO Biopolymer 625F and 3260HP from NatureWorks LLC, and LUMINY L105 from Total Corbion PLA.

[0025] The PMMA may be any suitable PMMA, such as those known in the art, and may have a Mw that varies over a wide range, such as from 10 kDa to 3 MDa, so long as the PMMA exhibits rheological behavior that allows for the desired degree of crystallinity (sufficient heat of fusion of enthalpy) of the semi-crystalline blend polymer of the PLA / PMMA semi-crystalline blend polymer. PMMA may also be produced that includes small percentages (e.g., less than about 5%, less than about 2%, or less than about 1%) of comonomers, such as those commonly used in the art (e.g., methyl acrylate, butyl acrylate, etc.), to improve one or more properties, such as impact strength or thermal stability. The melt flow rate of the PMMA may be any useful MFR for forming a semi-crystalline blend polymer and ultimately forming a laminated manufactured article therefrom. Typically, the MFR of the PMMA is one that, when combined with PLA, results in the desired heat of enthalpy and properties of the laminated manufactured article. Typically, the MFR of PMMA may be from 1, 2, 5, or 10 to 100, 50, 40, or 30 grams (230° C. / 10 min, 3.8 kg). Examples of PMMA that may be useful include those available from PLASKOLITE under the trade name CA41, and from Arkema under the trade names PLEXIGLAS VM, VS, and VSUVT.

[0026] The semi-crystalline blend polymer may include additional optional components that may be useful, for example, to produce a laminated manufactured article or to impart certain properties. It is understood that the optional components may be present in any useful amount, so long as the weight ratio of amorphous polymer / semi-crystalline polymer is within the ranges described herein. For example, the optional components may be from 1%, 2%, 5% or 10% by weight to 90%, 75%, 50% or 30% by weight of the semi-crystalline blend polymer and optional components.

[0027] Examples of optional ingredients include fillers, flow agents, and colorants, toners, extenders, colorants (e.g., pigments and dyes), lubricants, anticorrosive agents, thixotropic agents, dispersants, antioxidants, adhesion promoters, light stabilizers, organic solvents, surfactants, flame retardants, antistatic agents, plasticizers, or combinations thereof.

[0028] Surprisingly, it has been found that semi-crystalline blend polymers are particularly useful for producing substantially amorphous additive manufacturing articles, despite having sufficient crystallinity to allow printing of the article by successive fusion of powder layers. When referring to an additive manufacturing article that is amorphous, it is understood that this refers to the semi-crystalline polymer that is converted back to an amorphous polymer, as opposed to any optional components that exhibit crystallinity. In particular, the semi-crystalline blend polymers are useful for additive manufacturing methods that include subsequent fusion of particulates in and between powder layers by application of directed electromagnetic radiation, such as SLS. The additive manufacturing article may be heat treated, if desired, as described herein, to recrystallize the semi-crystalline blend polymer that is converted back to an amorphous state during additive manufacturing of the article. EXAMPLES

[0029] Example 1: A blended polymer is formed by mixing 85% by weight PMMA, commercially available from Plaskolite under the trade name CA-41, and 15% by weight PLA, commercially available from Total Corbion PLA under the trade name Luminy L-105, in a twin screw extruder having a 27 mm diameter barrel and a length to diameter ratio of 40 to 1 at 215-205°C and a rotation speed of 400 rpm to form cylindrical pellets having a diameter of 1-3 mm and a length of 2-4 mm. Figure 1 shows a DSC plot of the PLA used to make the blended polymer. The PLA has a crystallinity of about 42% as determined from the DSC plot of Figure 1. Figure 2 shows a DSC curve of the PMMA (Plaskolite CA-41) used to make the blended polymer, which does not exhibit any crystalline melting or recrystallization peaks. Figure 3 shows the DSC curve of the blended polymer. It is readily apparent from these curves that the blended polymer, like PMMA, is substantially amorphous.

[0030] To produce the semi-crystalline blended polymer, the blended polymer on the tray is heat treated at 155° C. for 30 hours in air in a convection oven. A DSC plot of the semi-crystalline blended polymer is shown in FIG. 4, and it can be seen that upon heating, the semi-crystalline blended polymer has a distinct enthalpy peak due to melting at a heat and peak temperature (interchangeably referred to herein as Tm) of about 10.5 Joules / gram enthalpy. The melting peak disappears upon cooling and reheating, indicating that the blended polymer reverts to an amorphous state.

[0031] The semi-crystalline blended polymer is freeze-milled using liquid nitrogen as a coolant. After milling, the powder has a D10 of 7.19 micrometers, a D90 of 26.07 micrometers, and a D50 of 11.01 micrometers, by number, after sieving out large particles and agglomerates greater than 250 micrometers. A flow aid, Aerosil A200 (fumed silica), is added to the powder at 0.5% by weight of powder and flow aid and mixed in a 20 liter Henschel mixer. Mixing in the Henschel mixer further reduced the particle size to D10, D50, and D90 of 7.23 micrometers, 11.38 micrometers, and 28.04 micrometers, respectively, to form a semi-crystalline blended polymer powder.

[0032] A Farsoon 252P SLS additive manufacturing printer is used to produce additive manufacturing articles using the powders mentioned above. The bed temperature is set at 122.5°C. This temperature is significantly lower than the Tm and melting onset temperature (beginning of the DSC melting peak) due to the small particle size. Additive manufacturing parts are printed with a test article as shown in Figure 5, which has some porosity, yet is somewhat transparent and exhibits good mechanical properties (2800 MPa modulus, 35 MPa tensile strength, and 1.5% elongation at break). Preferred embodiments of the present invention will be described below in detail. EMBODIMENT 1 1. A semi-crystalline blended polymer comprising an amorphous thermoplastic polymer and a thermoplastic semi-crystalline polymer, each of said polymers being substantially miscible with each other and blended in a weight ratio of amorphous polymer / semi-crystalline polymer of greater than 1 and up to about 20, wherein the blended semi-crystalline polymer exhibits a DSC melting peak enthalpy of at least about 3 Joules / g. EMBODIMENT 2 2. The semi-crystalline blended polymer of embodiment 1, wherein the weight ratio is from 10 to 2. EMBODIMENT 3 3. The semi-crystalline blended polymer of embodiment 2, wherein the weight ratio is from 10 to 3. EMBODIMENT 4 4. The semi-crystalline blend polymer of any one of claims 1 to 3, wherein the amorphous thermoplastic polymer has a glass transition temperature of about 60°C to about 120°C, and the semi-crystalline thermoplastic polymer has a melting temperature as determined by DSC of at least about 140°C. EMBODIMENT 5 5. The semi-crystalline blend polymer of embodiment 4, wherein the amorphous thermoplastic polymer has a glass transition temperature of about 100° C. to about 120° C. and the semi-crystalline thermoplastic polymer has a melting temperature, as determined by DSC, of ​​at least about 140° C. to about 200° C. EMBODIMENT 6 6. The semi-crystalline blend polymer of any one of the preceding claims, wherein the melting peak enthalpy of the semi-crystalline thermoplastic polymer is less than the melting peak enthalpy of the semi-crystalline blend polymer. EMBODIMENT 7 7. The semi-crystalline blend polymer of any one of claims 1 to 6, wherein the amorphous polymer is polymethyl methacrylate and the semi-crystalline polymer is a polyester. EMBODIMENT 8 9. The semi-crystalline blend polymer of embodiment 8, wherein the polyester is polylactic acid. EMBODIMENT 9 7. The semi-crystalline blend polymer of any one of the preceding claims, wherein the amorphous polymer is an amorphous polyamide and the semi-crystalline polymer is a semi-crystalline polyamide. EMBODIMENT 10 10. The semi-crystalline blended polymer of any one of the preceding embodiments, wherein the blended polymer has a melting temperature of at least about 140° C. EMBODIMENT 11 11. The semi-crystalline blended polymer of embodiment 10, wherein the blended polymer has a melting temperature of at least about 150° C. to about 225° C. EMBODIMENT 12 12. The semi-crystalline blended polymer of any one of the preceding claims, wherein the polymer is a powder having a D10 of at least 1 micrometer and a D90 of equivalent spherical diameter of up to 200 micrometers. EMBODIMENT 13 13. The semi-crystalline blended polymer of embodiment 12, wherein the powder has an equivalent spherical diameter D50 of about 20 micrometers to 100 micrometers. EMBODIMENT 14 14. The semi-crystalline blended polymer of any one of the preceding claims, wherein the blended polymer is substantially free of solvent. EMBODIMENT 15 1. A method of forming a semi-crystalline blended polymer comprising: a. melt blending an amorphous thermoplastic polymer and a thermoplastic semicrystalline polymer, each of said polymers being substantially miscible with each other at a weight ratio of amorphous polymer / semicrystalline polymer of greater than 1 to about 20 to form a blend polymer; and b. heat treating the blended polymer at a crystallization temperature above the glass transition temperature of the amorphous polymer but below the melting temperature of the semi-crystalline polymer for a heat treatment time sufficient to crystallize the blended polymer to achieve the semi-crystalline blended polymer; The method includes: EMBODIMENT 16 16. The method of embodiment 15, wherein the heat treating step is carried out for a heat treatment time of at least about 2 hours. EMBODIMENT 17 17. The method of embodiment 16, wherein the heat treatment time is at least about 4 hours to about 24 hours. EMBODIMENT 18 18. The method of any one of embodiments 15 to 17, wherein the blended polymer is substantially amorphous. EMBODIMENT 19 19. The method of any one of embodiments 15 to 18, wherein the semi-crystalline blend polymer has a DSC melting peak enthalpy of at least about 5 Joules / g and a melting temperature of at least about 140° C. EMBODIMENT 20 20. The method of any one of claims 15 to 19, wherein at least a portion of the heat treating step is carried out at a temperature below but within 20°C of the melting temperature of the semi-crystalline polymer. EMBODIMENT 21 21. The method of any one of embodiments 15 to 20, wherein the heat treating step is carried out at a heat treatment temperature of about 60° C. to about 200° C. EMBODIMENT 22 22. The method of embodiment 21, wherein the heat treatment temperature is from about 100° C. to about 180° C. EMBODIMENT 23 23. The method of embodiment 22, wherein the heat treatment temperature is up to about 175°C. EMBODIMENT 24 24. The method of any one of embodiments 15 to 23, wherein the melt blending step is carried out in an extruder. EMBODIMENT 25 25. The method of any one of claims 15 to 24, further comprising grinding the semi-crystalline blended polymer to form a powder. EMBODIMENT 26 26. The method of embodiment 25, wherein the grinding step is carried out at a temperature below -50°C. EMBODIMENT 27 1. A method of forming an additive manufactured article, comprising: a. spreading a layer of powder of the semi-crystalline blended polymer according to any one of embodiments 1 to 14; b. heating and fusing the particles of said layer in a controlled manner with directed electromagnetic radiation; c. spreading subsequent layers of the semi-crystalline blended polymer and fusing each layer to the previous layer in a controlled manner with directed electromagnetic radiation to form the laminated manufactured article; The method includes: EMBODIMENT 28 28. The method of embodiment 27, wherein the polymer of the layered manufactured article is substantially amorphous. EMBODIMENT 29 29. The method of claim 28, wherein the polymer of the layered manufactured article crystallizes when the layered manufactured article is exposed to heating above the glass transition temperature of the amorphous polymer for a period of at least 2 hours. EMBODIMENT 30 30. The method of any one of claims 27 to 29, wherein the method is selective laser sintering. EMBODIMENT 31 15. A laminated manufactured article comprising a semi-crystalline blended polymer according to any one of embodiments 1 to 14, which has been converted back to a substantially amorphous polymer. EMBODIMENT 32 32. The laminated manufactured article of claim 31, wherein the semi-crystalline blended polymer that has been reverted to amorphous recrystallizes upon heating to a temperature between the glass transition temperature of the amorphous polymer and the melting temperature of the semi-crystalline polymer.

Claims

1. 1. A semi-crystalline blended polymer comprising an amorphous thermoplastic polymer and a thermoplastic semi-crystalline polymer, each of said polymers being substantially miscible with one another and blended in an amorphous polymer / semi-crystalline polymer weight ratio of greater than 1 and up to 20, said blended semi-crystalline polymer exhibiting a DSC melting peak enthalpy of at least 3 Joules / g, said amorphous thermoplastic polymer having a glass transition temperature of 100°C to 120°C, and said thermoplastic semi-crystalline polymer having a melting temperature as determined by DSC of at least 140°C to 200°C.

2. The semi-crystalline blend polymer of claim 1 , wherein the weight ratio is from 10 to 2.

3. 2. The semi-crystalline blend polymer of claim 1, wherein said amorphous polymer is polymethylmethacrylate and said semi-crystalline polymer is a polyester.

4. 2. The semi-crystalline blend polymer of claim 1, wherein the amorphous polymer is an amorphous polyamide and the semi-crystalline polymer is a semi-crystalline polyamide.

5. The semi-crystalline blend polymer of claim 1 , wherein the blend polymer has a melting temperature of at least 140° C.

6. 6. The semi-crystalline blended polymer of any one of claims 1 to 5, wherein the polymer is a powder having a D10 of at least 1 micrometer, a D50 of 20 to 100 micrometers, and a D90 of equivalent spherical diameter of up to 200 micrometers.

7. 6. The semi-crystalline blended polymer of claim 1, wherein the blended polymer is substantially free of solvent.

8. 1. A method of forming a semi-crystalline blended polymer comprising: a. melt blending an amorphous thermoplastic polymer and a thermoplastic semi-crystalline polymer, each of said polymers being substantially miscible with each other at a weight ratio of amorphous polymer / semi-crystalline polymer of greater than 1 to 20 to form a blend polymer; and b. heat treating the blended polymer at a crystallization temperature above the glass transition temperature of the amorphous polymer but below the melting temperature of the semi-crystalline polymer for a heat treatment time sufficient to crystallize the blended polymer to achieve the semi-crystalline blended polymer, wherein at least a portion of the heat treating step is performed at a temperature below but within 20° C. of the melting temperature of the semi-crystalline polymer, the blended semi-crystalline polymer exhibiting a DSC melting peak enthalpy of at least 3 Joules / g; The method includes:

9. The method of claim 8 , wherein the heat treating step is carried out for a heat treatment time of at least 2 hours.

10. 9. The method of claim 8, wherein the blend polymer of step (a) is substantially amorphous and the semi-crystalline blend polymer has a DSC melting peak enthalpy of at least 5 Joules / g and a melting temperature of at least 140°C.

11. The method of claim 8, wherein the heat treating step is carried out at a heat treatment temperature of from 60°C to 200°C.

12. 12. The method of any one of claims 8 to 11, further comprising grinding the semi-crystalline blended polymer to form a powder.

13. A method for forming an additive manufactured article from a semi-crystalline blended polymer, comprising: a. spreading a layer of powder of a semi-crystalline blended polymer comprising an amorphous thermoplastic polymer and a thermoplastic semi-crystalline polymer, each of said polymers being substantially miscible with each other and blended in an amorphous polymer / semi-crystalline polymer weight ratio of greater than 1 and up to 20, said blended semi-crystalline polymer exhibiting a DSC melting peak enthalpy of at least 3 Joules / g; b. heating and fusing the particles of said layer in a controlled manner with directed electromagnetic radiation; c. spreading subsequent layers of the semi-crystalline blended polymer and fusing each layer to the previous layer in a controlled manner with directed electromagnetic radiation to form the laminated manufactured article; The method includes:

14. The method of claim 13 , wherein the polymer of the layered manufactured article is substantially amorphous.

15. 15. The method of claim 14, wherein the polymer of the layered manufactured article crystallizes when the layered manufactured article is exposed to heating above the glass transition temperature of the amorphous polymer for a period of at least 2 hours.

Citation Information

Patent Citations

  • Polylactic acid-based resin composition and sheet-like molding comprising the same

    JP2015155491A

  • Polyamide blends containing polyarylethers for laser sintering powders

    JP2019527639A

  • Graphic articles comprising semicrystalline polylactic acid-based films

    JP2019528327A

  • Apparatus for producing parts by selective sintering

    US5597589A

  • Polylactic acid resin composition, process for producing the same, biaxially stretched polylactic acid film, and molded articles thereof

    WO2004087812A1